Maternal features at time of preterm prelabor rupture of membranes and short-term neonatal outcomes. (3rd June 2022) - Alla, Sarada; Ramseyer, Abigail; Whittington, Julie R.; Peeples, Sara; Ounpraseuth, Songthip T.; Magann, Everett F.
Abstract: Objective: The objective of this study was to assess if maternal and obstetric characteristics other than gestational age at the time of rupture impact short-term neonatal outcomes. Methods: This is a retrospective observational study from a single tertiary care referral center. This study reviewed women with a singleton pregnancy complicated by preterm prelabor rupture of membranes over a 3-year period from May of 2014 through May of 2017. Maternal characteristics and short term neonatal outcomes were collected. Results: We identified 210 pregnancies complicated by preterm prelabor rupture of membranes. Eighteen of these patients had rupture of membranes prior to viability. Of the maternal characteristics at time of admission studied, gestational age at rupture and race influenced short term neonatal outcomes. Women who identified as race other than white had neonates with lower rates of intubation than neonates born to white patients. Gestational age at rupture significantly influenced the neonatal intensive care unit length of stay. Each additional week gained before rupture occurred was associated with a 17.1% decrease in length of stay. Maternal age, gravidity, parity, body mass index, single deepest pocket, and amniotic fluid index did not influence short term neonatal outcomes. Conclusions: Gestational age at rupture of membranes is the most predictive factor associated with short term neonatal outcomes. Race may also influence short term neonatal outcomes. Other maternal characteristics do not seem to influence short term neonatal outcomes. This information can assist with patient counseling on admission for preterm prelabor rupture of membranes and expected neonatal course.